The Influence of Work Behavior, Work Environment, and Social Interaction, on Job Satisfaction of Raja Pas Rantauprapat Minimarket Employees - Sri Akhirun Nisa; Ade Parlaungan Nasution; Daslan Simanjuntak (Quantitative Economics and Management Studies, 2022)
This study aims to determine the effect of work behavior, work environment and social interaction on job satisfaction of employees of Minimarket Raja Pas Rantauprapat. The population in this study were all employees at Minimarket Raja Pas Rantauprapat. The sample in this study was 36 people, the sampling was carried out using a saturated sampling technique or census sampling, where all members of the population were sampled. The object of this research is the result data regarding work behavior, work environment, and social interaction. The data analysis technique used is the classical assumption test, multiple linear regression test, hypothesis testing and the coefficient of determination. Data processing in this study was assisted using the IBM SPSS application. The results showed that work behavior had a positive and significant effect on employee job satisfaction at the Raja Pas Rantauprapat Minimarket, with a coefficient value of 0.202, the work environment positively and significantly affected employee job satisfaction at the Raja Pas Rantauprapat Minimarket with a coefficient value of 0.238 and social interaction significantly. positive and significant effect on employee job satisfaction at Raja Pas Minimarket with a coefficient value of 0.447. And work behavior, work environment and social interaction together have a positive and significant effect on job satisfaction for employees at the Raja Pas Rantauprapat Minimarket. work environment positively and significantly affects employee job satisfaction at Raja Pas Minimarket Rantauprapat with a coefficient value of 0.238 and social interaction positively and significantly affects employee job satisfaction at Raja Pas Minimarket with a coefficient value of 0.447. And work behavior, work environment and social interaction together have a positive and significant effect on job satisfaction for employees at the Raja Pas Rantauprapat Minimarket. work environment positively and significantly affects employee job satisfaction at Raja Pas Minimarket Rantauprapat with a coefficient value of 0.238 and social interaction positively and significantly affects employee job satisfaction at Raja Pas Minimarket with a coefficient value of 0.447. And work behavior, work environment and social interaction together have a positive and significant effect on job satisfaction for employees at the Raja Pas Rantauprapat Minimarket.